COLLABORATION BETWEEN THE TNI AND THE COMMUNITY IN THE 125TH UNITED ARMY TO BUILD VILLAGES (TMMD) PROGRAM TO IMPROVE THE QUALITY OF LIFE IN VILLAGES IN LUBUK GADANG NAGARI, SANGIR DISTRICT, SOLOK SELATAN REGENCY - Novita Sari; Irwan, Irwan; Yenita Yatim; Yenni Melia; Elvawati, Elvawati; Yushendra, Yushendra (CV KULTURA DIGITAL MEDIA, 2025)
The Manunggal Army to Build Villages (TMMD) program represents a tangible form of collaboration between the Indonesian National Armed Forces (TNI) and the community to accelerate rural development. The 125th TMMD program, implemented in Solok Selatan Regency, serves as a concrete example of strategic cooperation between the TNI, local government, and community in improving welfare and strengthening regional resilience. This study aims to describe the forms of cooperation between the TNI and the community in implementing the 125th TMMD program and to analyze its social and economic impacts. The study employs a qualitative descriptive method using a case study approach, through observation, documentation, and literature analysis. The results indicate that the collaboration between the TNI and the community in the 125th TMMD program is realized through two main aspects: physical and non-physical activities. Physical activities include the development and improvement of tourism infrastructure for Mount Kerinci hiking routes, renovation of uninhabitable houses, and construction of sanitation facilities in Nagari Lubuk Gadang Selatan, Sangir District. Non-physical activities consist of national defense education, community empowerment programs, and efforts to strengthen the spirit of mutual cooperation and nationalism. The implementation of the 125th TMMD program has significantly contributed to improving tourism accessibility, stimulating regional economic growth, and enhancing synergy between institutions and the community in sustaining development. Therefore, the TMMD program functions not only as a physical development initiative but also as an effective model of partnership that strengthens the bond between the TNI and the people. The program has proven effective in increasing community participation, strengthening social solidarity, and becoming a key factor in promoting equitable development in Solok Selatan Regency.